Reflections on China - Yunus, Muhammad (Lahore Services Book Club, 1988)
Examines how China has approached diplomacy, strategy, and negotiation throughout its history, and reflects on the consequences for the global balance of power in the twenty-first century
Include Index and Bibliography
Keywords: World Peace -- China